The Role of MSME on Unemployment in Indonesia - P. Eko Prasetyo , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Unemployment is one of the main problems of complex socio-economic development. This paper aims to analyze Schumpeter's theory of economic development to examine the "Schumpeter effect" and the "refugee effect". This research analysed empirical data on the growth of MSMEs and the unemployment rate in Indonesia. The data dimension used is the time series ratio data after the 2008 economic crisis, quarterly data for the 2009-2019 Q3 period. The main analysis results show that the Schumpeter effect is valid, and the refugee effect is less valid. This means that the growth of MSMEs can significantly reduce the unemployment rate, and there is a high unemployment rate due to the low growth of MSMEs. However, the existence of a high unemployment rate is not automatically able to trigger the growth of MSMEs, except only for micro businesses because these businesses do not require much investment capital or working capital.